The Concept of Gatekeepers Under the Digital Markets Act and Undertakings of Paramount Significance for Competition Across Markets in the GWB - Intersections and Differences - Dacar, Rok (Digital Platforms: Legal And Economic Challenges, 2024)
The article analyzes the concept of gatekeepers under the Digital Markets Act and companies that are of paramount importance in several markets according to Section 19a of the German Act Against Restraints of Competition (GWB). Both the Digital Markets Act and the provisions of Section 19a GWB represent examples of asymmetric regulation, meaning a type of regulation that imposes stricter obligations on companies with greater market power. The Digital Markets Act includes both quantitative and qualitative criteria for identifying gatekeepers that play a significant role in the market and operate core platform services. The provision of Section 19a GWB focuses on companies with exceptional significance across multiple markets and allows for the prohibition of certain behaviors without the need to prove a violation of competition rules. The article also addresses the potential conflict between the two acts.